ANALISIS PERILAKU PEJALAN KAKI PADA PENGGUNAAN FASILITAS PENYEBERANGAN DI SEPANJANG JALAN KAWASAN MALIOBORO YOGYAKARTA - Lilis Trianingsih, Retna Hidayah (Universitas Negeri Yogyakarta, 2014)
ABSTRACTThis study aims to provide information on the behavior of pedestrians using the crossingfacilities along the Malioboro in Yogyakarta and to describe the perception of pedestrians on thecrossing condition of the facilities available. This study used survey method. the type ofresearch design used in this research is descriptive qualitative research is to depict or describethe naturally occurring condition. While data collection is done through a literature study,observation, and interviews. The population of this research is all pedestrian with the number ofrespondents as many as 20 people and sample collection techniques are Snowball Sampling.There are three aspects of the indicator analysis study, namely: security and safety, comfort,and ease of access. The results of this study are descriptions of the various behaviors ofpedestrians in using the facilities crossings in terms of security and safety aspects, comfort, andease of access as well as describe the condition of the facilities crossings available, so it can beused as an input policy development and design facilities crossings better.Keywords: Crossing Facilities, Security and Safety, Walking Behavior